Association between the correct use of intranasal aerosols and symptom improvement in allergic rhinitis - Galindo Rodríguez, Gabriela; Chávez Jiménez, Karen Patricia; González Díaz, Sandra Nora; Macouzet Sánchez, Carlos; De Lira Quezada, Cindy Elizabeth (Sociedad Española de Inmunología Clínica, Alergología y Asma Pediátrica, 2025)
Objective: Allergic rhinitis (AR) is highly prevalent worldwide. Good patient adherence ensures successful treatment. This study aimed to identify the association between the intranasal aerosol technique and symptom improvement. Methods: This is an analytical, prospective, and longitudinal study that included 36 patients diagnosed with AR. The Rhinitis Control Assessment Test (RCAT) questionnaire was administered to both an experimental population and a control group. The 11 steps of the intranasal aerosol technique were explained to the experimental group, and performance was graded using a pamphlet for patient follow-up in subsequent controls. Results: Of the participants, 63.9% were women and 36.1% were men, with a median age of 30 years (IQR 24-42) and an age range from 18 to 69 years. An average RCAT percentage of 55.6% was observed in both groups during the first consultation. On the second visit, a difference in disease control was noted. In the experimental group, 83.3% had controlled symptoms, whereas only 61.1% of the control group did. At the third visit, 76.5% of the experimental group had controlled symptoms, compared to 58.8% of the control group. In the experimental group, 52.9% of patients demonstrated good technique, while only 5.9% in the control group did (p=0.004). Conclusions: Patient education and training, compared to an untrained group, benefit the patient by aiding in the remission of symptoms and improving quality of life.